Pengaruh Media Pembelajaran Audio Visual terhadap Hasil Belajar Siswa Kelas VII pada Mata Pelajaran Fiqih MTs di Kota Bogor - Amalia Hasanah; Sri Nurul Milla; Retno Triwoelandari (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
One of the factors that can affect learning outcomes is the use of learning media, one of which is audio-visual media. This study aims to determine the effect of using audio-visual learning media on the learning outcomes of class VII students in fiqh subjects at one of the MTS in Bogor City. This research method uses a quantitative method with a quasi-experimental design of the type of nonequivalent control group pretest-posttest design. Researchers obtained data from 50 students by conducting experiments through pretest and posttest tests in the control class and the experimental class. The results of this study indicate that there is an effect of using audio-visual learning media on the learning outcomes of class VII students in fiqh subjects at one of the MTS in Bogor City with an average learning improvement of 14.6 while the experimental class with an average learning improvement result of 23,8 and it is also proven by the Simple Paired T-Test, it is known that the significance value of the students' learning outcomes is = Sig. (2-tailed) 0.000 <0.05, which means that there is a significant effect so that the use of audio-visual learning media can improve student learning outcomes well. Keywords: influence, audio visual media, learning outcomes.